Efisiensi usaha akuakultur sistem mina padi kolam dalam di Kabupaten Minahasa Tenggara - Toar, Debby; Mudeng, Joppy D.; Watung, Juliaan Ch.; Longdong, Sammy N. J.; Kusen, Diane J.; Wantasen, Adnan S. (e-Journal BUDIDAYA PERAIRAN, 2021)
This study aimed to evaluate the efficiency of the aquaculture system of the deep water rice field aquaculture system in Southeast Minahasa Regency. The method used was survey method with the respondents were all cultivators who carry out the deep water rice field aquaculture system. The data collected included primary and secondary data, with data collection techniques of observation, interviews and literature study. Data analysis was done by combining qualitative and quantitative analysis. Quantitative data analysis carried out were revenue, income and efficiency and business feasibility. The results showed that the production of deep water rice field aquaculture system in Southeast Minahasa Regency for fish was 24,700 kg and rice 69,300 kg. The cost incurred was Rp. 499,392,000, - with a net profit of Rp. 487,707,998,-. The efficiency of deep water rice field aquaculture system in Southeast Minahasa Regency was 1.90 which means this business was said to be efficient, while the business feasibility value was 0.90 which means to continue deep water rice field aquaculture system business was needed to be considered